Perkembangan Peradaban Islam Pada Masa Bani Umayyah II Di Andalusia - lubis, adjie umair harvis; HSB, maulana sutan; Herlambang, Bagus; Matullesy, Fikri Maulana; Alfahrizy, Abdilbar (Tabayyun : Journal Of Islamic Studies, 2023)
This study explains how Islam developed during the Umayyad II era in Andalusia. The aim of this research is to find out more about the origins of the Umayyad Dynasty, Islamic civilization during the Umayyad era, as well as the factors that caused the decline and eventual destruction of the Umayyad Bani. The end result was the Umayyad dynasty, named after Umayyad Ibn 'Abdi Shams Ibn 'Abdi Manaf. This dynasty was actually founded during the reign of Caliph Uthman bin Affan, but only after the caliph was killed and Hasan ibn Ali was elected by the people, Iraqi Muslims handed over their power to Muawiyah through discussion and agreement. the unity of the Islamic world under one ruler. The year 41 AH (661 AD) was called the year of congregation ('Am al Jama'ah) at that time. And a number of factors contributed to the decline and destruction of the Umayyad Dynasty, such as the struggle for power within the royal family, ongoing hostility with Shiite and Khawarij opposition groups, ethnic conflicts between tribes in North and South Arabia, the inability of the people's caliphs to carry out his government. leading the government, and the tendencies of the rich. Bani Abbas, who received full support from Bani Hashim, the Shia group, and the Mawali group, overthrew the government.